Implementation and prospective evaluation of the Country Heart Attack Prevention model of care to improve attendance and completion of cardiac rehabilitation for patients with cardiovascular diseases living in rural Australia: a study protocol. Issue 2 (16th February 2022) - Beleigoli, Alline; Nicholls, Stephen J; Brown, Alex; Chew, Derek P; Beltrame, John; Maeder, Anthony; Maher, Carol; Versace, Vincent L; Hendriks, Jeroen M; Tideman, Philip; Kaambwa, Billingsley; Zeitz, Christopher; et al.
Abstract : Introduction: Despite extensive evidence of its benefits and recommendation by guidelines, cardiac rehabilitation (CR) remains highly underused with only 20%–50% of eligible patients participating. We aim to implement and evaluate the Country Heart Attack Prevention (CHAP) model of care to improve CR attendance and completion for rural and remote participants. Methods and analysis: CHAP will apply the model for large-scale knowledge translation to develop and implement a model of care to CR in rural Australia. Partnering with patients, clinicians and health service managers, we will codevelop new approaches and refine/expand existing ones to address known barriers to CR attendance. CHAP will codesign a web-based CR programme with patients expanding their choices to CR attendance. To increase referral rates, CHAP will promote endorsement of CR among clinicians and develop an electronic system that automatises referrals of in-hospital eligible patients to CR. A business model that includes reimbursement of CR delivered in primary care by Medicare will enable sustainable access to CR. To promote CR quality improvement, professional development interventions and an accreditation programme of CR services and programmes will be developed. To evaluate 12-month CR attendance/completion (primary outcome), clinical and cost-effectiveness (secondary outcomes) between patients exposed (n=1223) and not exposed (n=3669) to CHAP, we will apply a multidesign approach that encompasses a prospective cohort study, a pre-post study and a comprehensive economic evaluation. Ethics and dissemination: This study was approved by the Southern Adelaide Clinical Human Research Ethics Committee (HREC/20/SAC/78) and by the Department for Health and Wellbeing Human Research Ethics Committee (2021/HRE00270), which approved a waiver of informed consent. Findings and dissemination to patients and clinicians will be through a public website, online educational sessions and scientific publications. Deidentified data will be available from the corresponding author on reasonable request. Trial registration number: ACTRN12621000222842.